Protective effect of vitamine E and melatonin against radiation induced damage in testis of rat - Yalcinkaya, F. R.; Gokce, A.; Guven, E. O.; Davarci, M.; Cikim, G.; Yekeler, H.; Balbay, M. D. (Elsevier Science Bv, 2009)
[Abstract Not Available]